2021
DOI: 10.3389/fonc.2021.743655
|View full text |Cite
|
Sign up to set email alerts
|

Glioma Imaging by O-(2-18F-Fluoroethyl)-L-Tyrosine PET and Diffusion-Weighted MRI and Correlation With Molecular Phenotypes, Validated by PET/MR-Guided Biopsies

Abstract: Gliomas exhibit high intra-tumoral histological and molecular heterogeneity. Introducing stereotactic biopsy, we achieved a superior molecular analysis of glioma using O-(2-18F-fluoroethyl)-L-tyrosine (FET)-positron emission tomography (PET) and diffusion-weighted magnetic resonance imaging (DWI). Patients underwent simultaneous DWI and FET-PET scans. Correlations between biopsy-derived tumor tissue values, such as the tumor-to-background ratio (TBR) and apparent diffusion coefficient (ADC)/exponential ADC (eA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…In this study, significant differences between pHGGs and pLGGs can be observed on MRI images for restricted diffusion and ring enhancement. Restricted diffusion can provide information of the diffusion of microscopic water molecules in normal and diseased tissues 15,16 . In malignant tumors, due to the large nuclei of tumor cells, increased nuclear-to-cytoplasmic ratio, and tight cell arrangement, the intracellular and extracellular spaces are narrowed, and the diffusion of water molecules is restricted.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, significant differences between pHGGs and pLGGs can be observed on MRI images for restricted diffusion and ring enhancement. Restricted diffusion can provide information of the diffusion of microscopic water molecules in normal and diseased tissues 15,16 . In malignant tumors, due to the large nuclei of tumor cells, increased nuclear-to-cytoplasmic ratio, and tight cell arrangement, the intracellular and extracellular spaces are narrowed, and the diffusion of water molecules is restricted.…”
Section: Discussionmentioning
confidence: 99%
“…The 1p/19q codeletion and epidermal growth factor receptor mutations had lower ADC, and IDH1 mutations had higher TBR mean values. 25 FET-PET MR imaging predicted ATRX, MGMT, IDH1, and 1p19q mutations in 85%, 76%, 89%, and 98%, respectively. 26 Tumor Margin Delineation and Defining Tumor Extent for Radiation Therapy Planning.…”
Section: Clinical Indications For Pet Mr Imaging In Glioma Managementmentioning
confidence: 96%
“…In Europe, 18 F-FET is the most frequently used amino acid tracer for brain tumor imaging, and especially in Germany, some centers have collectively performed more than 20,000 examinations because of the high clinical interest in this method (11,12). Furthermore, the increasing number of publications coming from Australia, China, India, and South Korea indicate a wide acceptance of this method (13)(14)(15)(16)(17). For 18 F-FET, approval exists in Switzerland (18) and in France (IASOglio; IASON).…”
mentioning
confidence: 99%